Matrix Extension Study: Listeria Right Now™ Test for Detection of Listeria spp. from Selected Environmental Surfaces Without Enrichment: AOAC Performance Tested MethodSM 081802. (3rd December 2019) - Roman, Brooke; Mozola, Mark; Donofrio, Robert; Bastin, Benjamin; Klass, Nicole; Bird, Patrick M; Chen, Yi
Abstract: Background: Listeria Right Now™ is a novel, enrichment-free test for the detection of Listeria spp. in swab samples taken from environmental surfaces. Results are available in less than 1 h. In a previous Performance Tested Method SM (PTM) study, the test was validated for swab samples from stainless-steel and sealed concrete surfaces. Objective: A PTM matrix extension study was conducted to validate the method for the detection of Listeria spp. in swab samples from ceramic tile, plastic, and rubber surfaces. Methods: Performance of the Listeria Right Now method was compared to that of the U.S. Food and Drug Administration Bacteriological Analytical Manual reference culture procedure for the detection of Listeria spp. in swab samples taken from inoculated ceramic tile, plastic, and rubber surfaces. Data were analyzed using a probability of detection model. Results: There were no significant differences in performance between the Listeria Right Now and reference culture methods for any of the three surfaces tested, as determined by probability of detection analysis. Conclusions: The Listeria Right Now method is an effective procedure for the detection of Listeria spp. from a variety of environmental surfaces. Highlights: Listeria Right Now provides accurate results, without enrichment, in real time. This enables food industry personnel to react swiftly to suspected Listeria contamination incidents.